From knowledge to wisdom: Will wisdom management replace knowledge management? - Maria Jakubik; Peeter Müürsepp (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - This conceptual paper aims to contribute to the knowledge management (KM) literature by seeking to determine whether wisdom management (WM) will replace KM in future. Design/methodology/approach - This exploratory paper follows the interpretivist research philosophy and the deductive approach. The data collection is based on selected literatures from three disciplines (KM, philosophy and psychology). The findings were qualitatively analysed. Findings - The findings are threefold: (1) the discussion of wisdom has been either neglected or superficially discussed in the KM literature; (2) despite the fact that wisdom is widely discussed and researched in philosophy and psychology disciplines, there is no commonly agreed upon definition of wisdom, and a dichotomy exists between the implicit and explicit theories of wisdom; (3) wisdom research in philosophy and psychology disciplines provides valuable input to KM by identifying the dimensions, components and characteristics of wisdom and wise individuals. Research limitations/implications - Important sources may have been unintentionally overlooked in this paper. This paper identifies the need for empirical research and discussion about WM as the next potential phase of KM. It offers several implications for researchers, managers and management educators as this paper shows that WM is emerging as a new discipline. Originality/value - This paper makes a theoretical contribution to the fifth phase of KM by drawing attention to wisdom and WM as the next potential phase of KM.
Keywords: 650; Data-information-knowledge-wisdom (DIKW); Intelligence; Knowledge management (KM); M10 (General business administration); Wisdom; Wisdom management (WM)